HADLN: Hybrid Attention-Based Deep Learning Network for Automated Arrhythmia Classification - Jiang, Mingfeng; Gu, Jiayan; Li, Yang; Wei, Bo; Zhang, Jucheng; Wang, Zhikang; Xia, Ling (Frontiers in Physiology, 2021)
In recent years, with the development of artificial intelligence, deep learning model has achieved initial success in ECG data analysis, especially the detection of atrial fibrillation. In order to solve the problems of ignoring the correlation between contexts and gradient dispersion in traditional deep convolution neural network model, the hybrid attention based deep learning network (HADLN) method is proposed to implement arrhythmia classification. The HADLN can make full use of the advantages of ResNet and Bi-LSTM architecture to obtain fusion features containing local and global information, and improves the interpretability of the model through the attention mechanism. The method is trained and verified by using the PhysioNet 2017 challenge dataset. Without loss of generality, the ECG signal is classified into four categories, including atrial fibrillation, noise, other and normal signals. By combining the fusion features and the attention mechanism, the learned model has a great improvement in classification performance and certain interpretability. The experimental results show that the proposed HADLN method can achieve precision 0.866, recall 0.859, accuracy 0.867 and F1-score 0.880 on 10-fold cross-validation.